Otto Leichter. Briefe ohne Antwort Aufzeichnungen aus dem Pariser Exil für Käthe Leichter 1938-1939 - Berger, Heinrich (2003)
The text at issue written by Otto Leichter for his wife from September 1938 to August 1939 in his Exile in Paris is a unique documentation of the inside view of the loss of a beloved person during the time of one year. In addition to that the diary in letters is of great historic and social importance because both, the writer and the addressee were important persons in Austrian history, who were threatened as Social Democrats and by the race laws of Nuremberg as Jews. In the diary in letters Otto Leichter reported about his living conditions in the exile in Paris. Different to papers which were written for a greater group of readers, the author did not have to show consideration for other people. He could write down his real opinions and estimations but also his needs and aversions. So Otto Leichter reported about himself, his social surroundings, his view of the political development but also about Käthe Leichter and his relationship to her but also about her frame of mind in view of the various reprisals. We can see continuity as his longing for her, his hope for a reunion and his keen mind in political interests. But we also see the break in his relationship to political companions and the great loss of his trust in European politics. In addition to that we can observe how Otto Leichter vacillated between very realistic political analyses and the resulting despair and his desperately cling to the hope for reunion. His manifold description of problems caused by the separation is firstly a documentation of suffer, but it also marks the strong connection between the two partners. Otto Leichter lost his closest reliable person, the mother of his children, his sexual partner and his most important political companion, and he suffered very hard on the separation. Käthe Leichter, the real addressee could not ever see these words (she was murdered at concentration camp in 1942), but the diary in letters is a really extraordinary source for historical research, that should be available for a greater number of readers as scientific edition.